Inkontinensia Urin Pascapersalinan dan Faktor-Faktor Risiko yang Memengaruhinya - Edy Fakhrizal; Sri Wahyu Maryuni (Fakultas Kedokteran Universitas Riau, 2016)
Postpartum urinary incontinence is an important and often overlooked form of maternal morbidity. The aim of thisstudy is to obtain prevalence of postpartum urinary incontinence and its influential risk factors. This is an observationalstudy. The subjects were all primipara stayed in Obstetric & Gynecology of Arifin Achmad Pekanbaru – Riau hospital,between July 1st and December 31st 2014. The data of risk factors (demographic and obstetric) was obtained frommedical records and cough test was done too. The data was analyzed with computerized statistic data analysis 12 (Stata 12 ). The distribution of data were analyzed with descriptive univariate and presented in (n) and (%). Bivariateanalysis was done to see any influential risk factors to postpartum urinary incontinence event. The prevalence ofurinary incontinence in this study was 30% and the influential risk factors were BMI, body weight changing duringpregnancy, delivery mode, birthweight and length of second stage.